Expression features of hybrid gene of frog antimicrobial peptide and staphylococcal bacteriophage K endolysin in bacteria Еsсherichia coli - Sovgir, Natalia V.; Golenchenko, Sergey G.; Prakulevich, Vladimir A. (Experimental Biology and Biotechnology, 2017)
The aim of this study was cloning and expression analysis of hybrid gene consisted of frog (Rana esculenta L., 1758) antimicrobial peptide esculentin gene and the Myoviridae family staphylococcal bacteriophage K endolysin gene in Е. coli cells. Primers to fuse esculentin and staphylococcal bacteriophage K endolysin genes were designed to obtain the chimeric protein with His-tag at the C-terminus. The hybrid gene was cloned in E. coli cells and sequenced. The subsequent analysis of gene expression revealed the intracellular accumulation of fusion protein esculentin-C / endolysin KHis. Recombinant protein accumulated in E. coli cells predominantly in the insoluble form, but some of protein molecules remained soluble and exhibited antistaphylococcal activity. Applications: biotechnology, molecular biology, pharmaceutics.
Keywords: antimicrobial peptides; esculentin; staphylococcal bacteriophage K endolysin; fusion protein; antistaphylococcal activity; CFU (colony forming unit)